(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
A number of studies conducted revealed a number of factors militating against large scale production of maize in the study area to include among other things such as low soil fertility, low and poorly distribution of rainfall, nonuse of optimum plant density, poor implementation of improved Agronomic practices and use of indigenous local and often un improved maize varieties. An experiment comprised of three NPK fertilizer rates, four intra -row spacings and three maize varieties was undertaken. The treatments were arranged in a Split plot design with fertilizer rates and intra row spacings assigned to main plot and varieties in the sub plot using three replications. Results obtained revealed that each increase in NPK fertilizer from 200 to 400 kg ha-1 significantly produced taller plants, longer ear height, heavier 100- grain weight, and grain yield while number of days to 50% tasseling became reduced with increased in NPK fertilizer rates. Each increase in intra- row spacing from 20 to 50 cm significantly enhanced all the growth and yield attributes of the crop. SAMMAZ 40 maize variety significantly produced taller plants, longer ear height and took longer days to attain days to 50% tasseling, higher 100-grain weight, and grain yield than the other two varieties that were statistically similar. It can be concluded that for good growth and yield, use of SAMMAZ 40 maize variety, use of 400 NPK kg ha-1 planted at 20 or 25 cm intra row spacings could be recommended to farmers at Samaru.